Social credit system improvement via technology mediation - Saaidin, Husna; Anuar, Faizul Nizar; Mohamed, Nurashikin Nazer; Gadiman, Nur Suriayanti; Ali, Syahrul Anuar; Nordin, Mohd Norazmi (Turkish Online Jounal of Qualitative Inquiry, 2021)
In the west, amazon inc. Has been criticized for introducing a mass surveillance system in its warehouses that monitors employees’ productivity, time off task, and is capable of dismissing employees without input from a human supervisor. This study seeks to find out how governments and corporations can implement a democratic technologically mediated social credit systemto maintain the trust relationship between themselves and citizens or employees, including the consequences of implementing surveillance systems in the workplace. This will be conducted using an interpretivist research philosophy to capture an in-depth explanation of the social credit phenomenon and to form an understanding of the meanings that are created by the implicated entities. Through a deductive reasoning process and a qualitative research approach, the author will determine eleven (11) entities that are crucial for the successful implementation of a democratic technologically mediated social credit system that will enhance the trust relationship between a state and its citizens, and between a corporation and its employees